Design, Development and Testing of Banana Fiber Extraction Machine - Prashant Shinde, Dr. Pramod Magade, Dr. Sushilkumar B. Magade (Mathematical Statistician and Engineering Applications, 2022)
Banana fibers are an excellent alternative to the synthetic materials that are often used in today’s society, thus their use should be encouraged. Banana fibers are natural goods that are both biodegradable and favorable to the environment. There are around 5 million hectares dedicated to the production of bananas in India. The separation of natural fibers is a time-consuming process, and the quality of the end result might differ significantly depending on the extraction technique used. The banana fibre extraction machine is created and built in order to reduce the amount of time needed for the process while simultaneously improving the overall quality of the finished product. This device improved the quality of fiber by changing the design of blades. The sharpness of the blades was damaging fibers, hence, sharpness has been reduced by providing radius or chamfers to the blades. Also, distance between rollers decides the pressure applied onto the pseudo stem, which helps for the separation of fiber from waste of pseudo stem. As low as this distance is, we get good fiber. Also, the motor torque should be sufficient enough to rotate blades at optimum speed to crush pseudo stem.